2007
DOI: 10.1186/1744-859x-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anxiety disorders: a population-based epidemiological study in metropolitan area of Casablanca, Morocco

Abstract: BackgroundIn Morocco, no epidemiological study has been conducted to show the current prevalence of mental disorders in the general population. The aim of the present study was to assess the prevalence and comorbidity of anxiety disorders in Moroccan subjects.MethodsWe used cross-sectional study, with a representative sample of Casablanca city. Direct interviews used the Mini International Neurpsychiatric Interview in its validated Moroccan Arabic versionResultsAmong 800 subjects, 25.5% met criteria of at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 20 publications
2
31
0
1
Order By: Relevance
“…In terms of diagnostic criteria, the only other study conducted in a representative sample of the Moroccan general population investigated anxiety disorders in a sample of 800 adults in Casablanca and reported an overall prevalence of 25.5%. A high prevalence of obsessive–compulsive disorder (OCD) was found both in this study [6.1% (2)] and in the survey reported here (6.6%).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In terms of diagnostic criteria, the only other study conducted in a representative sample of the Moroccan general population investigated anxiety disorders in a sample of 800 adults in Casablanca and reported an overall prevalence of 25.5%. A high prevalence of obsessive–compulsive disorder (OCD) was found both in this study [6.1% (2)] and in the survey reported here (6.6%).…”
Section: Discussionsupporting
confidence: 62%
“…In a study on a representative sample of the adult population of Casablanca, Kadri et al. (2) found a prevalence of anxiety disorders of 25.5%. The prevalence estimates for disorders related to alcohol and substance misuse were also in accordance with the results of another study in a representative sample of the adult population of Casablanca conducted by Kadri et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kadri et al, 2007 (10) found prevalence of anxiety disorders in general population using MINI. Prevalence of panic disorder, generalized anxiety disorder social phobia in general population 2%, 4.3%, 3.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Согласно данным одного из американских исследований [13], показатель распространенности тревожных расстройств в течение года среди общей популяции составляет 18,1%, а в течение жизни -28,2%, что значительно больше, чем распространенность любого другого психического расстройства [14]. В исследовании, проведенном в Марокко [15], распространенность этого заболевания в течении года оказалась более высокой по сравнению с приведенными выше цифрами -25,5%.…”
Section: тревогаunclassified